"Ask Me What I Want": Community-based participatory research to explore transition-age foster Youth's use of support services. (January 2020) - Ruff, Saralyn C.; Harrison, Kristi
Highlights: This study used community-based participatory research to examine transition-age foster youth's perceptions of service provision. Both the participatory research process and results of the study indicate the importance of honoring the autonomy of transition-age youth in care, both in research and in service delivery. Transition-age youth responding to our survey had used at least one formal support service, but also reported barriers to formal service use, including mistrust of the system, fear of diagnosis, and lack of hope about change. Results regarding formal and informal supports suggest the importance of continuity during changes in placement, and augmenting youth's informal supports, particularly peers. Abstract: Transition-age foster youth are a population deserving support, including possible psychological assessment and service provision. The majority of these youth do not receive adequate supports and face difficulties in the transition to adulthood. To understand the challenges and barriers to care, the majority of research relies on adult stakeholders rather than on the voices of youth themselves. This study used community-based participatory research to design and implement a survey of transition-age foster youth to learn about their experiences in foster care, use of professional services, barriers to initiating and continuing services, perspectives on treatment topics and therapist characteristics, and use of informal supports. This study details the methods and application of community-based participatory research with foster youth, and then presents a subset of the results of the survey completed by 84 youth transition-age youth in care. Findings indicate the importance of working towards equitable relationships with youth in care to inform research on youth's experiences and perceptions. Survey results affirm transition-age foster youth's desire for autonomy, their resourcefulness, and potential areas where services for these youth could offer more support, particularly during periods of transition.